Effects of lead on the visual system of occupationally exposed subjects. - Cavalleri, Alessandro; Trimarchi, F.; Gelmi, C.; Baruffini, A.; Minoia, Claudio; Biscaldi, G.; Gallo, G. (Scandinavian Journal of Work, Environment & Health, 1982)
A quantitative measurement of visual field in mesopic adaptation was performed for 35 workers occupationally exposed to lead and 35 referents matched for age, smoking, and alcohol consumption. The mean level (+/- SD) of lead in blood was 47 +/- 16 microgram/100 ml (2.25 +/- 0.77 mumol/l) [range 21-82 microgram/100 ml (1.01-3.94 mumol/l)]. In 10 exposed subjects a central scotoma was found that was not evidenced in any of the referents. A highly significant decrease in visual sensitivity was observed for the exposed subjects a central scotoma was found that was not evidenced in any of the referents. A highly significant decrease in visual sensitivity was observed for the exposed subjects. The results point to damage of central and peripheral optic nerve fibers. In the most severe cases, central vision is preferentially affected, and therefore the results are suggestive of subclinical optic neuropathy.